Variability, Correlation and Path Coefficient Analysis for Agro-morphological Traits in Wheat Genotypes (Triticum aestivum L.) under Normal and Heat Stress Conditions - Poudel, Mukti Ram; Poudel, Padam Bahadur; Puri, Ramesh Raj; Paudel, Hema Kumari (International Journal of Applied Sciences and Biotechnology, 2021)
Assessment of variability and traits association in crop help to enhance selection efficiency. Therefore, the present investigation entitled “Variability, Correlation and Path Coefficient Analysis for Agro-morphological Traits in Wheat Genotypes (Triticum aestivum L.) under Normal and Heat Stress Conditions” was carried out during winterseason of 2019/2020 at Institute of Agriculture and Animal Science (IAAS), Bhairahawa, Nepal to identify traits that highly contribute to grain yield and suitable for its further improvement. The experiment was laid out following alpha lattice design with two replications. The twentygenotypes of wheat was sown in two different environments viz., irrigated and heat stress in November 29, 2019 and December 25, 2019 respectively. It was found that under normal condition, moderate GCV and PCV were recorded in SW, TGW, NGPS, and WGPS. Under heat stress condition, high GCV and PCV were observed in GY. High heritability and high GAM was observed in TGW & GY, NGPS, WGPS, TGW under normal and heat stress condition respectively. Under normal condition SW exhibited positive correlation and high positive direct effect on GY at genetic level and WGPS at phenotypic level. And under heat stress condition SW exhibited positive correlation and high positive direct effect on GY. Whereas, at phenotypic level, WGPS and PH exhibited high positive direct effect on grain yield. Hence it is clear that spike weight and weight of grains per spike are important traits for grain yield improvement. Int. J. Appl. Sci. Biotechnol. Vol 9(1): 65-74